Trajectory analysis of the coronavirus pandemic and the impact of precautionary measures in the Kingdom of Bahrain. Issue 1 (1st January 2021) - Al Dallal, Ahmed; Al Dallal, Jehad; Alnaser, Waheeb E.; Ashqar, Mohammed Y.; Al-Anzi, Bader S.
Abstract: The Kingdom of Bahrain announced its first case of COVID-19 infection on February 24, 2020. Since that time, the government has imposed several restrictions such as closures, banning gatherings, and closing border crossings to limit the spread of the pandemic and relieve pressure on the healthcare system. This article provides an overview of the current trajectory of the pandemic in the Kingdom of Bahrain. In addition, the article introduces and applies a methodology to analyze the impact of the interventions and precautionary measures enforced by the government to limit the COVID-19 disease propagation. The results show that most of the enforced precautionary measures were effective in reducing the spread of the disease by a percentage ranging from 20.2% to 41.8%. A religious occasion in Bahrain—involving large gatherings—had increased the spread of the disease by 28.7%. Not enough evidence is found to conclude that reopening interventions had caused the disease to spread again.